Expanded profiling of Remdesivir as a broad-spectrum antiviral and low potential for interaction with other medications in vitro - Sheli R. Radoshitzky; Patrick Iversen; Xianghan Lu; Jing Zou; Suzanne J. F. Kaptein; Kelly S. Stuthman; Sean A. Van Tongeren; Jesse Steffens; Ruoyu Gong; Hoa Truong; Annapurna A. Sapre; Huiling Yang; et al. (Scientific Reports, 2023)
Abstract Remdesivir (GS-5734; VEKLURY) is a single diastereomer monophosphoramidate prodrug of an adenosine analog (GS-441524). Remdesivir is taken up by target cells and metabolized in multiple steps to form the active nucleoside triphosphate (GS-443902), which acts as a potent inhibitor of viral RNA-dependent RNA polymerases. Remdesivir and GS-441524 have antiviral activity against multiple RNA viruses. Here, we expand the evaluation of remdesivir’s antiviral activity to members of the families Flaviviridae, Picornaviridae, Filoviridae, Orthomyxoviridae, and Hepadnaviridae. Using cell-based assays, we show that remdesivir can inhibit infection of flaviviruses (such as dengue 1–4, West Nile, yellow fever, Zika viruses), picornaviruses (such as enterovirus and rhinovirus), and filoviruses (such as various Ebola, Marburg, and Sudan virus isolates, including novel geographic isolates), but is ineffective or is significantly less effective against orthomyxoviruses (influenza A and B viruses), or hepadnaviruses B, D, and E. In addition, remdesivir shows no antagonistic effect when combined with favipiravir, another broadly acting antiviral nucleoside analog, and has minimal interaction with a panel of concomitant medications. Our data further support remdesivir as a broad-spectrum antiviral agent that has the potential to address multiple unmet medical needs, including those related to antiviral pandemic preparedness.